A stable pillared-layer Cu(ii) metal–organic framework with magnetic properties for dye adsorption and separation. (19th April 2017) - Yang, Liu; Li, Xiao; Sun, Chun-Yi; Wu, Han; Wang, Chun-Gang; Su, Zhong-Min
Abstract : A pillared-layer metal–organic framework can be used to separate rhodamine B (RB) and methylene blue (MB) dye molecules in a short amount of time. Abstract : By using a new N-donor ligand, a 3D stable pillared-layer metal–organic framework, namely [Cu4 (1, 4-ndc)4 (L)2 ]·H2 O·2DMF (1 ), has been synthesized under solvothermal conditions (1, 4-H2 ndc = 1, 4-naphthalenedicarboxylate; L = 1-(1-(1 H -imidazol-1-yl)naphthalen-4-yl)-1 H -imidazole). X-ray single crystal diffraction analysis was utilized to obtain the crystal structure of1 and1 was further characterized by elemental analysis, powder X-ray diffraction (PXRD), thermogravimetric analysis (TGA) and infrared spectroscopy (IR). Based on dinuclear Cu(ii ) clusters as nodes, compound1 is a 6-connected two-fold interpenetratingpcu network. Moreover, using rhodamine B (RB) and methylene blue (MB) as examples, 1 has the ability to separate dye molecules. Finally, the magnetic properties of1 have been investigated.